2008
DOI: 10.1002/ejsp.507
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate intentions to apply to the Northern Ireland Civil Service: the application of a theory of planned behaviour model

Abstract: The modern literature regarding the theory of planned behaviour (TPB) supports the distinction between self-efficacy (SE) and perceived behavioural control (PBC, Ajzen, 2002). This study compared an extended TPB model (ETPB), incorporating a measure of SE, against the more traditional theory of reasoned action (TRA) and TPB models. In the historically recent context of fair participation and equal opportunity legislation, undergraduate behavioural intentions to apply to the Northern Ireland Civil Service (NICS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…27(p401) Subjective norms refer to an individual's perceptions of others' desires that he/she perform a particular behavior, whereas perceived behavioral control focuses on an individual's perception of the ease or difficulty of performing a given behavior. 27 Ajzen 29 in 2002 proposed that the TPB introduced by Ajzen 24 in 1991 be modified by separating the construct of perceived behavioral control into two separate constructs: self-efficacy and controllability. Cammock et al 27 called this new model the ETPB and concluded that the ETPB proved a superior model over the TRA and conventional TPB in that it ''accounted for 60% of the variance in behavioral intentions.''…”
Section: Conceptual Framework/ Research Gapmentioning
confidence: 99%
See 4 more Smart Citations
“…27(p401) Subjective norms refer to an individual's perceptions of others' desires that he/she perform a particular behavior, whereas perceived behavioral control focuses on an individual's perception of the ease or difficulty of performing a given behavior. 27 Ajzen 29 in 2002 proposed that the TPB introduced by Ajzen 24 in 1991 be modified by separating the construct of perceived behavioral control into two separate constructs: self-efficacy and controllability. Cammock et al 27 called this new model the ETPB and concluded that the ETPB proved a superior model over the TRA and conventional TPB in that it ''accounted for 60% of the variance in behavioral intentions.''…”
Section: Conceptual Framework/ Research Gapmentioning
confidence: 99%
“…28 Whereas TRA considers behavior only as influenced by attitude and subjective norms, TPB adds perceived behavioral control as a third construct affecting behavior. 27 According to Cammock et al, 27 attitude reflects ''an individual's favorable or unfavorable evaluation of a particular behavior.'' 27(p401) Subjective norms refer to an individual's perceptions of others' desires that he/she perform a particular behavior, whereas perceived behavioral control focuses on an individual's perception of the ease or difficulty of performing a given behavior.…”
Section: Conceptual Framework/ Research Gapmentioning
confidence: 99%
See 3 more Smart Citations